How will training traders contribute to improved food safety in informal markets for meat and milk? A theory of change analysis - Johnson, Nancy L.; Mayne, John; Grace, Delia; Wyatt, Amanda (International Food Policy Research Institute, 2015)
Increased consumption of meat, milk, eggs, and fish among poor consumers in developing countries has the potential to improve nutrition as well as drive pro-poor economic development. However, animal-source foods are a major source of food-borne disease. In addition to the health impacts, concerns about food safety can reduce consumption of nutritious foods and reduce market access for smallholders. Researchers from the International Livestock Research Institute and partners have developed and piloted an institutional innovation—a training, certification, and branding scheme for informal value chain actors—that has the potential to improve the safety of animal-source foods sold in informal markets. To support further research and, eventually, delivery at scale, this paper develops a theory of change for how the intervention is expected to contribute to better nutrition and health outcomes for consumers. The outcomes along the pathway from intervention to impact are identified, along with the underlying causal assumptions. For each assumption, the existing evidence is summarized and assessed. The results show that for some parts of the impact pathway, outcomes and causal links are well defined and supported by evidence, while for others, the program logic needs to be refined and more evidence gathered to validate hypothesized causal relationships in specific contexts. Addressing these gaps through research and through piloting interventions with development partners can increase the likelihood of achieving expected outcomes and contribute to learning about how to improve the performance of informal markets in developing countries.